Vitamin and HbA1C Status in Tuberculosis Patients with Diabetes and its Association - Singh, Dr. Charanpreet (International Journal of Innovative Research in Medical Science, 2018)
Diabetes mellitus (DM)-tuberculosis is associated with poor glycemic control in DM patients. 2. DM is the most common risk factor associated with tuberculosis (TB); TB is also the third cause of death due to non-communicable disease (NCD). Materials and Methods: Present study was conducted in Dept. of TB and Chest Vedanta Institute of Medical sciences, Vedanta Hospital. A total of 100 patients of Type 2 DM were enrolled in the study of which 60 were male and 40 were female. Written consent was obtained from each patient to participate in the study. The study will be conducted in the patients admitted in the Department of TB and Chest in collaboration with Dept. of Biochemistry, Intensive Coronary Care Unit at Vedanta Hospital. All patients of DM with TB infection are diagnosed by clinician and admitted in our hospital for treatment. Informed consent was taken from all patients, who participated in our study and the study was approved by the college ethics committee. Blood pressure, height, body weight, and waist and hip circumferences of each patient were measured as an anthropometric and dietary measurement. Body mass index (BMI) and ratios of waist to hip circumference was calculated. Blood pressure of each patient was measured after giving rest for at least 5 min. Results: HbA1C levels were higher in the selected group of DM + TB patients mean value being 8.1 ± 0.56 %. There was a significant difference in Vit. B12 levels between cases (218.15 ± 35.65) and controls (355.02 ± 23.39), where serum level was low in cases compared to control group. About 13(18.88%) patients had Vit. B12 level less than 150pg/ml and 28(40.58%) were lying in the intermediate level between 150pg/ml to 350pg/ml. Serum vit.B12 levels ranged from 118pg/ml to 315pg/ml. 25(OH) D3 levels were 17.09 ± 2.15 ng/ml in study group where as in control group the levels were found to be 22.88±4.01.The BMI was higher in those suffering from DM+TB (28.13± 3.24) in comparison to normal subjects (24.89 ± 3.95). Conclusion: Our study has showed high prevalence of TB-DM co-burden of disease in our hospital settings and TB+DM TB-DM were significantly associated with age. Also it is concluded that vitamin D is a link between PTB and DM. Vitamin D levels are lower in patients with TB with DM. This study recommends the importance of performing diabetes screening among pulmonary TB patients and further similar studies needs to be done to determine the feasibility of TB-DM co-management.